Assessing the variation in leaf nutrient concentrations of oil palm (Elaeis guineensis) germplasms - BEHERA, SANJIB KUMAR; MATHUR, RAVI KUMAR; SURESH, KANCHERLA (The Indian Journal of Agricultural Sciences, 2019)
Leaf samples were collected from 17th frond of 157 palms comprising 52 accessions of teneras and Cameroon, Guinea Biassau, Zambian and Tanzanian duras available in the field gene bank of ICAR-Indian Institute of Oil Palm Research, Pedavegi, Andhra Pradesh, to assess the variation in leaf nutrient concentrations of oil palm (Elaeis guineensis Jacq.) germplasm. Collected leaf samples were processed and analysed for nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), sulphur (S) and boron (B) concentration. Leaf nutrient concentrations varied widely across the germplasm. Cameroon (0. 88%), Zambian (0. 91%) and Tanzanian (0. 98%) duras recorded higher leaf K concentration compared to Guinea Bissau duras and teneras. The teneras like 118×57, 134×57, 29×155, 139×155 and D×N (Deli×Nigeria) recorded higher leaf S concentration. Among the Zambian duras, ZS-1, ZS-3 and ZS-5 accessions recorded higher leaf K concentration, whereas ZS-2, ZS-3, ZS-6 and ZS-8 accessions had higher leaf Ca concentration. These findings could play a vital role in identification and development of nutrient efficient oil palm germplasm.